INNOVATIVE ASPECTS OF FORMATION OF COMPETITIVENESS OF FOOD INDUSTRY ENTERPRISES - LAGODIIENKO, V.; ZAVGORODNII, A.; LAHODIYENKO, V. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Mechanisms for increasing competitiveness are provided mainly through the constant generation and implementation of innovations. Taking into account the role and place of the food industry in the national economy, the innovative orientation of development becomes an undoubted condition for ensuring and maintaining the competitiveness of not only this industry, but the entire industry. The structure-forming nature of the functioning of the industry and the decisive importance in ensuring the country’s food security actualizes the problem of increasing the competitiveness of food industry enterprises on the basis of enhancing innovation. The purpose of the article is to study the role and importance of innovative factors in increasing the competitiveness of food industry enterprises. The study of innovative aspects of ensuring the competitiveness of business entities in the food industry is based on the use of a systematic approach, methods of economic and statistical analysis, an abstract logical method. The article substantiates the relationship between the development of food industry enterprises on an innovative basis with the possibilities of ensuring their competitiveness. Unfavorable trends in the implementation of innovative activities of business entities were revealed: a decrease in the number and share of innovatively active enterprises, the inefficiency of the structure of innovation costs. It has been established that the industry is dominated by the vector of technical re-equipment of production, since the overwhelming majority of innovation spending is directed to the purchase of machinery and equipment. The dynamics and correlation of the introduction of process and product innovations by food industry enterprises are analyzed. The results of the study of innovative activity in the food industry show that these processes have not reached the proper level, which negatively affects the competitiveness of enterprises in the industry, and there are no tendencies for significant changes towards improvement. The intensification of innovation activities of food industry enterprises requires an integrated approach and the formation of an innovation policy, taking into account modern development trends in the innovation sphere, which will help to overcome the technological gap and form a high level of competitiveness.